2017
DOI: 10.4136/ambi-agua.2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of humic substances extracted from freshwater and peat of different apparent molecular sizes

Abstract: This paper compares the structural characteristics of aquatic humic substances (AHS) with humic substances from peat (HSP) through different analytical techniques, including elemental analysis, solid state 13 C cross polarization/magic-angle-spinning nuclear magnetic resonance spectroscopy ( 13 C CP-MAS NMR), ultraviolet/visible (UV/Vis) spectroscopy and Fourier transform infrared (FTIR) spectroscopy and total organic carbon (TOC). The AHS were extracted from water collected in a tributary of the Itapanhaú Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The degree of aromaticity is dependent on the humification of humic substances and represented by a low E 4 /E 6 ratio, showing that little humificated residue is present (Saab and Martin-Neto, 2007). Rigobello et al (2017) reported that the E 4 /E 6 ratio is influenced by molecule size, environmental pH, levels of oxygen, carbon and carboxyl groups, and the age of the humic material. This affects the formation of humic substances, which, according to Stevenson (1994), occurs through three mechanisms: a) microbiological activity releases nitrogenated compounds that react with lignins; b) oxidation of polyphenolic compounds to form quinones that are condensates in reactions with aminated compounds, and c) reduction of sugars that react with aminated compounds and change into macropolymers of dark in color and with high molecular mass.…”
Section: H Nuclear Magnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…The degree of aromaticity is dependent on the humification of humic substances and represented by a low E 4 /E 6 ratio, showing that little humificated residue is present (Saab and Martin-Neto, 2007). Rigobello et al (2017) reported that the E 4 /E 6 ratio is influenced by molecule size, environmental pH, levels of oxygen, carbon and carboxyl groups, and the age of the humic material. This affects the formation of humic substances, which, according to Stevenson (1994), occurs through three mechanisms: a) microbiological activity releases nitrogenated compounds that react with lignins; b) oxidation of polyphenolic compounds to form quinones that are condensates in reactions with aminated compounds, and c) reduction of sugars that react with aminated compounds and change into macropolymers of dark in color and with high molecular mass.…”
Section: H Nuclear Magnetic Resonancementioning
confidence: 99%
“…Thus, humic fractions tend to increase particle cohesion and aggregate stability, and are associated with the distribution of aggregate particle sizes and conservation of carbon in the soil (Huang et al, 2010;Loss et al, 2016). Examining the spectral characteristics of separate fractions of organic matter can provide important information on how to improve soil quality (Oades et al, 1987;Rigobello et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with CK-L, L-An showed lower C/N and higher H/C and O/C ratios, which indicated that more N-containing compounds, carbohydrates and carboxylic acid derivatives, and a smaller aromatic fraction. An increase in the H content indicated a greater proportion of aliphatic C moieties (CH2) than aromatic C moieties (C = C) [15]. During the culture period, the H content of L-An gradually increased from 26.8 to 27.8 g kg −1 , which also confirmed the occurrence of lignin degradation due to the increase in aliphatic C.…”
Section: Elemental Composition Of Microbial Residuementioning
confidence: 65%
“…The H/C ratios show the degree of maturity of the HSs since indirectly, it reflects the presence of more condensed aromatic rings or substituted ring structures. The O/C ratio is considered an indicator of the contents of carbohydrates and carboxylic acid derivatives [15]. As shown in Table 1, the C, H, O + S contents of C-An were all significantly lower than those of CK-C, but C-An had higher N content.…”
Section: Elemental Composition Of Microbial Residuementioning
confidence: 99%
“…Humic acids have been discovered to be connected with aggregate particle size distribution and soil carbon preservation in order to improve particle cohesion and aggregate stability [4]. By studying the spectrum properties of different fractions of SOM, it can provide significant information on how to improve soil quality [14,15]. The use of species diversity in agricultural management substantially increases the quality of SOM, thus effectively influencing the relationship between soil aggregates [16].…”
Section: Introductionmentioning
confidence: 99%